Board Attributes and Financial Performance of Food and Beverage Companies Quoted on the Nigerian Stock Exchange (Lapai Journal of Economics, 2020)
The study examines the impact of board attributes on financial performance of Food and Beverage companies quoted on the Nigerian Stock Exchange. The study examines board attributes namely; Board size, board independence and board gender diversity. The study employs three measures for financial performance; Return on equity, Return on assets and Tobin q.  The longitudinal research design was adopted for the study. Secondary data was sourced from the annual reports and accounts of the companies for the period of study which is 2010-2018. Preliminary analysis such as descriptive statistics, correlation and multicollinearity analyses were first conducted. Next, the estimations were initially conducted using the individual performance variables and then we proceeded to a more robust estimation aggregating the individual variables into a performance index using the Principal Component Analysis (PCA). The findings revealed that board size, Board independence, Board gender diversity have statistically significant effects on corporate financial performance. The study recommends that corporate governance is a very germane aspect that companies must focus on if they expect to see improvements in performance.